The labour market performance of young return migrants after the crisis in CEE countries : the case of Estonia; Noorte ajutise migratsiooni seos nende hilisema edukusega tööturul kriisijärgselt Kesk- ja Ida-Euroopa riikides Eesti näitel - Maryna Tverdostup; Jaan Masso (The labour market performance of young return migrants after the crisis in CEE countries : the case of Estonia, 2015)
This paper extends the earlier literature on the effects of return migration by studying selection and labour market performance in terms of the wages of young returnees in particular. The topic is motivated by young people's various labour market issues and their high exposure to the consequences of the recent financial crisis. We use the Estonian Labour Force Survey data and the Estonian Population and Housing Census 2011 data in combination with the Estonian Tax and Customs Office data on individual payroll taxes. The econometric analysis focuses on the selection to temporary migration and estimation of wage premium to return, along with the decomposition of the returnee-stayer wage gap using the Oaxaca-Blinder approach and an investigation of wage premium dynamics over time after the return. The results generally show higher returns from temporary labour migration for young people relative to older people, and among youth the share of the unexplained fraction of the wage premium is also higher. These results imply a stronger role of experience gained abroad on earnings for youth.
2472293-5; 588751316